Review on effects of performance, emission and combustion characteristics of emulsified fuel in bifuel engine. (2018) - Gopidesi, Radha Krishna; Premkartikkumar, S.R.
The emission norms of diesel engines are turned more stringent due to continuous increasing of environmental pollutants. Thus, global researchers explore to reduce emissions from diesel engines by fulfilling the performance parameters. The major emissions in the diesel engines are the NOx emissions due to the higher combustion temperatures. Generally, dual fuel engines play a vital role in regulating both emission and performance parameters. Diesel engines are converted to dual fuel mode by using the various techniques such as blend, fumigation, and emulsion. Among these, water-diesel emulsion (WiDE) also can lessen the emissions of NOx and other pollutants promptly. It is observed that the combination of emulsified fuel and the gaseous fuels showed a simultaneous improvement in the thermal efficiency and reduction of NOx emissions. Various emulsion preparation techniques and effects of different gaseous fuels used with emulsified fuels in bifuel engines have been reviewed in this paper.